62.3k views
0 votes
Find the inverse of each given functions h(x)=2x-4/3

2 Answers

4 votes

Answer:

h^-1(x) = (3x+4)/2

answer choice c

User Gulshan Aggarwal
by
6.9k points
4 votes

Answer:


h(x')=(x)/(2) +(2)/(3)

Explanation:

We are given the following function:


h(x)=2x-(4)/(3)

To find the inverse of this function, we will put this function equal to y (another variable) and then make x the subject of it.


y=2x-(4)/(3)


y+(4)/(3) =2x


(y)/(2) +(4)/(6) =x


x=(y)/(2) +(2)/(3)

Now changing back the variable y to x to make it the inverse of h(x) to get:


h(x')=(x)/(2) +(2)/(3)

Therefore, the inverse of the given function h(x) is
h(x')=(x)/(2) +(2)/(3).

User Miao
by
6.1k points